MONOCLONAL GAMMOPATHY A THREE YEAR STUDY ON PARAPROEINEMIAS - Wahid, Mukhtar Ahmad; Abraham, George Kuruppacheril; Hamid, Saud Abu (Journal of Ayub Medical College Abbottabad, 1992)
ABSTRACT Sera from 22 patients (16 males + 6 females) with electrophoretically and immunologically secured diagnosis of monoclonal gammopathy were tested for various biochemical parameters. The final clinical diagnosis showing gamma-globulinemias in them was in the order of multiple myeloma (MM) 20 nos, Waldenstrom macroglobulinemia (MW) 1 no. and light chain disease (LCD) 1 no. The incidence of plasma cell neoplasm among Saudis is not very rare. The predominant type is IgG myeloma (74%) with a kappa to lambda ratio of 2: 1. Bence Jones Proteinuria is comparatively less common. Elevated levels of gamma glutamy l transpeptidase (GGT) in a good number of patients indicate the high occurrence of hepatic involvement in such patients.